CRISTA-NF observations in the vicinity of the polar vortex - Kalicinsky, Christoph (2018)
CRISTA-NF (Cryogenic Infrared Spectrometers and Telescope for the Atmosphere - New Frontiers) is an infrared limb sounder operated aboard the Russian high-altitude research aircraft M55-Geophysica. The instrument measures thermal emissions of the atmosphere in the spectral range from 4 – 15 µm between flight altitude ( ≈ 20 km) and around 5 km. CRISTA-NF successfully participated in a large polar aircraft campaign within the EU FP7- project RECONCILE (Reconciliation of essential process parameters for an enhanced predictability of Arctic stratospheric ozone loss and its climate interactions) in Kiruna (Sweden) from mid-January to mid-March in 2010. The preparation of the instrument for the campaign including calibration measurements as well as performing the measurements during the campaign were part of this work. The limb emission spectra measured by CRISTA-NF are used to detect polar stratospheric clouds (PSCs) and analyse their composition (NAT, STS, ice). PSCs were observed during the first five flights of the campaign (2010-01-17 – 2010-01-25). A polar stratospheric ice cloud, located above flight altitude during the first flight, is identified by means of the measurements and meteorological data. The observation of polar stratospheric clouds composed of (or clearly dominated by) a large amount of small NAT particles (mean radii < 3 µm) can be excluded by means of the analysis. The CRISTA-NF measurements enable the derivation of several trace gas volume mixing ratios (e.g. CFC-11, O 3 , HNO 3 ) with an unprecedented vertical resolution of around 500 – 600m (or even less for CFC-11) for several kilometres below flight altitude and a horizontal sampling along flight direction of ≈ 15 km. Comparisons with in-situ and remote sensing measurements illustrate the quality of the retrieved volume mixing ratios. Flight 11 of the aircraft campaign, which took place on March 2 in the vicinity of the polar vortex, is analysed in detail. The observations of the polar vortex (including the bottom edge of the vortex) and two filaments of different origin are presented. By means of O 3 -CFC-11- relations these filaments are clearly identified as one vortex and one non-vortex filament. The obtained results are compared with simulations by CLaMS (Chemical Lagrangian Model of the Stratosphere) to assess the model performance in terms of transport and chemical processes. CLaMS is capable of simulating even small scale transport structures. But the comparisons indicate an underestimation of the ozone depletion inside the vortex. Additionally, a model concept using artificial tracers, which enables the differentiation of air masses with respect to their origin, is validated. The date of the artificial tracer initialisation is very important to obtain simulation results, which are comparable to the observations. These tracers can be used to obtain additional information about the air mass origin. Furthermore, the artificial tracers are used to determine the impact of a vortex split event in December 2009 on the composition of air masses inside the vortex. CRISTA-NF (Cryogenic Infrared Spectrometers and Telescope for the Atmosphere - New Frontiers) ist ein Infrarot-Horizontsondierer, der an Bord des russischen Höhenforschungsflugzeuges M55-Geophysica eingesetzt wird. Das Instrument misst thermische Emissionen der Atmosphäre im Spektralbereich von 4 - 15 µm zwischen Flughöhe ( ≈ 20 km) und ungefähr 5 km. CRISTA-NF hat erfolgreich an einer großen polaren Flugzeugmesskampagne innerhalb des EU FP7-Projekts RECONCILE (Reconciliation of essential process parameters for an enhanced predictability of Arctic stratospheric ozone loss and its climate interactions) in Kiruna (Schweden) von Mitte Januar bis Mitte März 2010 teilgenommen. Die Vorbereitung des Instruments auf die Kampagne einschließlich der Kalibrationsmessungen, sowie die Durchführung der Messungen während der Kampagne waren Bestandteil dieser Arbeit. Die von CRISTA-NF gemessenen Emissionsspektren werden verwendet, um polare Stratosphärenwolken (PSCs) zu erkennen und ihre Zusammensetzung (NAT, STS, Eis) zu untersuchen. PSCs wurden während der ersten fünf Flüge der Kampagne (17.01. – 25.01.2010) beobachtet. Mit Hilfe der Messungen und meteorologischen Daten kann eine stratosphärische Eiswolke, die sich während des ersten Fluges oberhalb der Flughöhe befand, identifiziert werden. Die Beobachtung von polaren Stratosphärenwolken, die aus einer großen Anzahl von kleinen NAT-Teilchen (mittlerer Radius < 3 µm) bestehen (oder klar dominiert sind), kann mit Hilfe der Analyse ausgeschlossen werden. Die Messungen ermöglichen die Bestimmung der Mischungsverhältnisse mehrerer Spurengase (z.B. CFC-11, O 3 , HNO 3 ) mit einer bis jetzt unerreichten vertikalen Auflösung von ungefähr 500 – 600m (oder weniger für CFC-11) über mehrere Kilometer unterhalb der Flughöhe und einem horizontalen Sampling von ≈ 15km entlang des Flugpfades. Vergleiche mit insitu- und Fernerkundungsmessungen bestätigen die Qualität der bestimmten Mischungsverhältnisse. Flug 11 der Kampagne, der am 2. März im Bereich des Polarwirbels stattfand, wird im Detail untersucht. Während des Fluges wurden der Polarwirbel (einschließlich der Unterkante) und zwei Filamente unterschiedlicher Herkunft beobachtet. Diese Filamente werden mit Hilfe von O 3 -CFC-11-Relationen eindeutig als ein Vortexfilament und ein Filament anderer Herkunft indentifiziert. Die erzielten Ergebnisse werden mit CLaMS (Chemical Lagrangian Model of the Stratosphere) Simulationen verglichen, um die Leistungsfähigkeit des Modells hinsichtlich Transport und chemischen Prozessen zu beurteilen. CLaMS ermöglicht die Simulation sehr kleinskaliger Transportprozesse. Die Vergleiche zeigen aber eine Unterschätzung des Ozonverlusts im Polarwirbel. Zusätzlich wird ein Modellkonzept, das künstliche Tracer verwendet und die Unterscheidung von Luftmassen bezüglich ihrer Herkunft ermöglicht, überprüft. Der Initialisierungszeitpunkt dieser Tracer ist dabei von großer Bedeutung, um Simulationsergebnisse zu erhalten, die vergleichbar zu den Beobachtungen sind und zusätzliche Informationen über die Luftmassenherkunft liefern. Zudem werden die künstlichen Tracer verwendet, um die Auswirkung eines Wirbelsplits im Dezember 2009 auf die Luftmassenzusammensetzung innerhalb des Wirbels zu bestimmen.